What do small formats have to do with the paths of puppetry training in Brazil today? (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
The article discusses the presence of small-format puppet theaters within the most recent Brazilian theater scene in light of the transformations in the conditions of presentation and contemporary Brazilian cultural habits. It evokes the role to be played by higher education institutions in the Arts in Brazil and ends with a brief report on an experience the author had with the Extension Course Laboratório de Criação de Cenas Curtas em Teatro de Animação (Short Scene Creation Laboratory in Puppet Theater) and the project of circulation in bars and similar spaces called Cabaré Animado (Animated Cabaret).
Keywords: puppetry; small-format puppet theatre; Lambe Lambe Theatre; cultural habits; children's theatre; circulation circuits in puppet theatre